Norovirus and Foodborne Disease, United States, 1991–2000 - Widdowson, Marc-Alain (Centers for Disease Control and Prevention, 2005)
Efforts to prevent foodborne illness target bacterial pathogens, yet noroviruses (NoV) are suspected to be the most common cause of gastroenteritis. New molecular assays allow for better estimation of the role of NoV in foodborne illness. We analyzed 8,271 foodborne outbreaks reported to the Centers for Disease Control and Prevention from 1991 to 2000 and additional data from 6 states. The proportion of NoV-confirmed outbreaks increased from 1% in 1991 to 12% in 2000. However, from 1998 to 2000, 76% of NoV outbreaks were reported by only 11 states. In 2000, an estimated 50% of foodborne outbreaks in 6 states were attributable to NoV. NoV outbreaks were larger than bacterial outbreaks (median persons affected: 25 versus 15), and 10% of affected persons sought medical care; 1% were hospitalized. More widespread use of molecular assays will permit better estimates of the role of NoV illness and help direct efforts to control foodborne illness.